Use of MALDI-TOF Mass Spectrometry to Assay the Transthyretin V30M Mutation in Serum From a Liver Transplant Donor - Lacerda, Pedro C. (2016)
Familial amyloidotic polyneuropathy (FAP), Portuguese type, or ATTR V30M is an autosomal dominant inherited disorder caused by a mutation in the transthyretin gene, with a valine/methionine substitution at position 30 (TTRV30M). ATTRV30Mis characterized by a progressive sensory/autonomic polyneuropathy and multiple organ dysfunction. Liver transplantation is the main therapeutic option,as it virtually eliminates the production of circulating TTR V30M, which occurs predominantly in the liver.